Relação entre pontas de aplicação, horário de aplicação e cultivares no controle de Phakopsora pachyrhizi em soja - Moreira, Marcelo Temp (2010)
The process of agricultural production in Brazil has as a main gear the application of chemicals carried out by spraying machines. This study aimed to identify possible interactions between the tips of spraying nozzles, application time and fungicides on the control of Asian soybean rust (Phakopsora pachyrhizi Sidow) in three different cultivars. The work was carried out in Itaara - RS, spray nozzles used were XR 11002 (jet plan expanded use), TX 8002 (empty cone), TT 11002 (turbo fan), TJ60 11002 (twin flat) and AI 11002 (fan anti-drift). Applications were made at 8:00, 10:00 and 12 hours with fungicides cyproconazole+picoxystrobin and epoxiconazole+pyraclostrobin in R1 growth stage and repeated the second application 21 days after first in cultivars M-SOY 8000 RR, AL 72 and Agiara. Analysis of variance revealed a significant interaction between cultivars, spray nozzles and the application time for all variables, showing that several factors affect application technology. The increase of grain yield promoted by fungicides, in the average of application times ranged between nozzles, according to the cultivar. The cultivar AL 72 results showed the smallest variation between nozzles. The increase in grain yield promoted by treatments with different nozzles ranged between 37.39 and 45.75% for the fungicide pyraclostrobin + epoxiconazole and 32.38 and 39.34% for the fungicide ciproconzaol + picoxystrobin